A 5MW direct-drive generator for floating spar-buoy wind turbine: Development and analysis of a fully coupled Mechanical model. (November 2014) - Sethuraman, Latha; Xing, Yihan; Gao, Zhen; Venugopal, Vengatesan; Mueller, Markus; Moan, Torgeir
This work forms the first of a two-part investigation aimed at identifying the challenges and opportunities of implementing a direct-drive generator for a spar-buoy type floating wind turbine. Preliminary specifications are presented for a fully coupled aero-hydro-servo-elastic model of a floating wind turbine with a 5 MW direct-drive generator. The drive-train model uses a low-speed, high-torque radial flux permanent magnet generator supported by two main-shaft bearings. The mechanical properties of the drive-train, including the main dimensions, mass of major nacelle equipment and details for the hub/nacelle assembly are presented. The rationale behind the adjustments to the tower and platform properties and the motivation to selection of best arrangement that is appropriate for supporting the developed system is explained. A discussion on the development of the variable speed-variable pitch control system suitable for the direct-drive system including modifications to avoid negative damping and blade-pitch instability are presented. Fully coupled simulations for the developed aero-hydro-servo elastic model were carried out in HAWC2 for the normal operating conditions of the wind turbine. The aerodynamic response of the model was verified and compared with that of a geared floating wind turbine system. Some initial results comparing the main shaft loads of the land-based and floating versions of the direct-drive wind turbine suggest satisfactory dynamic behaviour of the drive-train. The results prompt further research using a detailed drive-train model to verify the internal response, loading and durability of the components to assess their compatibility with a floating wind turbine system.